The Quality of Wingko Babat from Green Bean Flour - Prananta, Alvina Restu; Holinesti, Rahmi (Jurnal Pendidikan Tata Boga dan Teknologi, 2022)
Wingko is an intermadiate morsture food or snack made from glutinous rice flour mixed with grated half young coconut then added sugar. The main ingredient in making wingkobabat is glutinous rice flour. Wingko tripe variations can be done by diversifying with local agricultural products, namely mung bean flour. The nutritional content of mung bean flour is not inferior to glutinous rice flour. This study discusses the analysis of the quality (shape, color, aroma, texture and taste) of wingko tripe with mung bean flour as much as 10%, 20%, and 30%. This type of research is a pure experiment with a completely randomized design method (CRD) with three treatments and three repetitions. The data used is primary data obtained directly from 5 expert panelists who provide answers from a questionnaire (organoleptic test format) on the quality of greenbean flour wingko babat. The data that has been obtained is then tabulated in the form of a table and an Analysis of Variance (ANOVA) is performed. If the analysis of variance shows Fcount Ftable, then it is continued with Duncan's test. The results showed that the substitution of mung bean flour had an effect on the quality of color, texture, taste and had no effect on the shape and aroma of wingko tripe with mung bean flour. The results of the quality test of wingko tripe with mung bean flour are the best in treatment (X1) with 10% mung bean flour substitution.